Dasar Filosofis Tujuan Pendidikan Nasional Indonesia: Kajian Atas Nilai-Nilai Pancasila dalam Sistem Pendidikan - Anisa Tata Ilahi; Agus Tinus (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to examine the philosophical foundations of Indonesia's national education goals through an analysis of Pancasila values within the education system. Indonesia's national education cannot be separated from the ideological foundation of Pancasila, which serves as the spirit and direction of national development. This study employs a qualitative approach using library research methods, relying on primary and secondary sources including legislation, government regulations, and relevant scientific literature. The findings reveal that the five principles of Pancasila have a strong and complementary correlation as the philosophical foundation of education: the First Principle affirms the spiritual dimension and piety; the Second Principle emphasizes the formation of civilized and humane individuals; the Third Principle promotes national unity and identity; the Fourth Principle develops democratic character and deliberation; and the Fifth Principle directs education toward the realization of social justice. The implications of this study call for a reconstruction of educational orientation to be more holistically grounded in Pancasila values, not merely achieving cognitive competencies. These findings are expected to serve as an academic contribution to the development of more nationally characterized curriculum policies.